The relationship between service recovery fairness, customer emotional responses and customer behavioral responses in fitness clubs - Lee, Kyongmin; Jun, Hyung-pil (Journal of Asian Scientific Research, 2025)
The previous research has failed to comprehensively examine the relationship between the negative emotional responses of customers and negative customer behaviors that may arise despite efforts towards service recovery fairness. Accordingly, this study investigated the relationship between service recovery fairness and customers’ emotional responses by classifying members of a fitness club who encountered service failure into positive and negative categories. A survey was carried out to gather data from members of fitness clubs in Korea who have encountered service failures using a convenience sampling method. Service recovery fairness had a positive influence on customers’ favorable emotions and a negative effect on their unfavorable emotions. It was discovered that positive emotions had a positive effect on intentions to recommend and loyalty while having a negative impact on intentions to switch upon investigating the impact of customers’ emotional responses on their behavioral responses. Conversely, negative emotions were shown to have a negative impact on intentions to recommend and loyalty, yet a positive impact on intentions to switch. Fitness clubs must enhance service recovery fairness after a service failure to manage customer emotions and establish long-term relationships.